Lin's Uncommon Life - Shackelford, Scott; Castle, Emily (Book collections on Project MUSE., 2023)
"Elinor (Lin) Ostrom's life was an incredible journey. Being the first woman ever to win a Nobel Prize in Economics was an achievement of a lifetime. But it was just the culmination of a life spent struggling against the odds.Even while overcoming childhood hardships and a stutter and being denied opportunities because she was a woman, Lin never lost sight of the wonders around her and was always curious to learn more. Lin would teach generations of students the lessons she learned through a lifetime of research and dedication. As Lin said "little by little, bit by bit, family by family, so much good can be done on so many levels."Discover Lin's Uncommon Life, and let it be an inspiration to follow your own path. Small steps, taken one at a time, can lead you somewhere truly uncommon in the end"--